The electric vehicle routing problem and its variations: A literature review. (November 2021) - Kucukoglu, Ilker; Dewil, Reginald; Cattrysse, Dirk
Highlights: A literature review on the electric vehicle routing problem is introduced. A systematic classification is presented. Existing solution approaches for the electric vehicle routing problem are summarized. Potential research directions are pointed out. Abstract: Electric vehicle technology is promising to reduce both the costs and environmental impact of logistics operations. Consequently, much research is being carried out in this field. On the operational level, the electric vehicle routing problem (EVRP) has recently been introduced and deals with forming effective route plans for vehicles while satisfying a set of battery-related restrictions. This paper presents a comprehensive literature review of the EVRP and its extensions. In this context, 136 published papers that consider the routing of battery electric vehicles are reviewed. The EVRP is clearly defined, variations on the basic EVRP are discussed, a mathematical formulation, which also models several simple variations of the problem, is given, and developed solution approaches are discussed in detail. In addition, EVRP benchmark sets are presented, and, lastly, interesting future research directions are discussed.